A case report of wandering spleen with pedicle torsion and splenic infarction being misdiagnosed as organ inversion complicated with acute appendicitis - Zhao, Shengjie; Wang, Yindi; Wan, Zhiheng; Chen, Hancheng; Zhao, Xinyu; Li, Ruibin (Frontiers in Surgery, 2022)
Free spleen is a rare disease that is easily misdiagnosed. When combined with splenic pedicle torsion and even splenic infarction, free spleen is a rare and critical cause of surgical acute abdomen. We report an 18-year-old male patient with abdominal organ inversion diagnosed as acute appendicitis before operation. Laparoscopic exploration confirmed free spleen with splenic pedicle torsion led to splenic infarction and was complicated by appendicitis. He was treated with laparoscopic appendectomy and abdominal splenectomy. The patient recovered well after the operation and was discharged from the hospital in 7 days. During the 4-year follow-up, there was no report of complicated infections such as pneumonia or sepsis.